2018
DOI: 10.1111/nyas.13845
|View full text |Cite
|
Sign up to set email alerts
|

Nonerosive reflux disease: clinical concepts

Abstract: Esophageal symptoms can arise from gastroesophageal reflux disease (GERD) as well as other mucosal and motor processes, structural disease, and functional esophageal syndromes. GERD is the most common esophageal disorder, but diagnosis may not be straightforward when symptoms persist despite empiric acid suppressive therapy and when mucosal erosions are not seen on endoscopy (as for nonerosive reflux disease, NERD). Esophageal physiological tests (ambulatory pH or pH-impedance monitoring and manometry) can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 145 publications
(302 reference statements)
0
7
0
1
Order By: Relevance
“…Gastroesophageal reflux disease (GERD) is a chronic condition characterized by a heterogeneous spectrum of typical and atypical symptoms, of which heartburn is the most common symptom. 1,2 As proton-pump inhibitors (PPIs) are effective in improving GERD-related heartburn, response to empiric PPI therapy is used clinically to confirm GERD diagnosis in the absence of alarm symptoms, despite limited specificity due to overlap with functional esophageal disorders. [3][4][5] However, many patients respond only partially or do not respond to an 8-week course of full-dose PPI.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastroesophageal reflux disease (GERD) is a chronic condition characterized by a heterogeneous spectrum of typical and atypical symptoms, of which heartburn is the most common symptom. 1,2 As proton-pump inhibitors (PPIs) are effective in improving GERD-related heartburn, response to empiric PPI therapy is used clinically to confirm GERD diagnosis in the absence of alarm symptoms, despite limited specificity due to overlap with functional esophageal disorders. [3][4][5] However, many patients respond only partially or do not respond to an 8-week course of full-dose PPI.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Gastroesophageal reflux disease (GERD) is a chronic condition characterized by a heterogeneous spectrum of typical and atypical symptoms, of which heartburn is the most common symptom 1,2 …”
Section: Introductionmentioning
confidence: 99%
“…Like much of modern medicine, gastroesophageal reflux disease (GERD) is not a homogeneous disorder, but rather is caused by a myriad of mechanisms resulting in similar symptoms. Disparate mechanisms believed to play a role in disease burden include hiatal hernia (HH), increased transient lower esophageal sphincter (LES) relaxation, hypotensive LES, abnormal motility leading to impaired clearance, xerostomia, impaired swallowing, impaired gastric emptying, acid hypersecretion, mucosal disruption/permeability, and hypersensitivity 42–45 . An argument could be made that FLIP may play a role in the evaluation of EGJ distensibility and esophageal motility, both of which are believed to be key mechanisms in GERD; however, FLIP certainly does not test for all the proposed reflux mechanisms, nor is it an adequate test of mucosal integrity or acid burden.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…54 pH monitoring has been shown to be a useful subsequent study to diagnose non-erosive reflux disease in cases with normal mucosal findings on EGD. 36,55 A retrospective study of 10 SSc patients with reflux referred for lung transplant 56 found that abnormal pH was predictive for lower 1-year survival rates.…”
Section: Objective Evaluationmentioning
confidence: 99%